Power-Management Strategies for a Grid-Connected PV-FC Hybrid System (International Journal of Engineering and Computer Science, 2015)
This paper presents a method to operate a grid connected hybrid system. The hybrid system composed of a Pho-tovoltaic (PV) array and a Proton exchange membrane fuel cell (PEMFC) is considered. The PV array normally uses a maximum power point tracking (MPPT) technique to continuously deliver the highest power to the load when variations in irradiation and temperature occur, which make it become an uncontrollable source. In coordination with PEMFC, the hybrid system output power becomes controllable.Two operation modes, the unit-power control (UPC) mode and the feeder-flow control (FFC) mode, can be applied to the hybrid system. The coordination of two control modes, the coordination of the PV array and the PEMFC in the hybrid system, and the determination of reference parameters are presented. The proposed operating strategy with a flexible operation mode change alwaysoperates the PV array at maximum output power and the PEMFC in its high efficiency performance band, thus improving the performance of system operation, en-hancing system stability, and decreasing the number of operating mode changes.